Acute kidney injury after cardiac surgical operations specially including coronary artery bypass graft operations - Lipski, Adam; Szymoniak-Lipska, Marta; Greberski, Krzysztof (Journal of Medical Science, 2015)
Introduction. Acute kidney injury as abrupt loss of kidney function leads to accumulation nitric and non-nitric metabolites, toxins. It coexists with deep disorder of fluid balance. Most of cardiac surgical operations are performed using extracorporeal circulation (ECC). To the main risk factors of the postoperative dysfunction of kidneys belong: age above 70, congestive heart failure, previous CABG, preoperative creatinine concentration 124–177 µmol/L, diabetes type I, glucose concentration > 16,6 mmol/L, EEC longer than 3 hours and decreased cardiac output (CO).Material and methods. The serum creatinine is not enough sensitive marker to diagnose early period of acute kidney injury because the serum creatinine increase occur later than true GFR changes and it needs time to accumulate. It depends on factors like: age, sex, weight, hydration status and what patient eat. NGAL (neutrophil-gelatinase associated lipocalin), cystatin C, KIM-1, IL-18, L-FABP are new markers of acute kidney injury which better than the serum creatinine concentration correspond with kidney injury. The risk factors of the acute kidney injury (AKI) are kidney hypoperfusion, microembolisation by bubbles or material particles and significant activation of humoral factors.Results. One of the methods reducing mortality CSA-AKI (cardiac surgery associated kidney injury) is renal replacement therapy (RRT), which should be used in early period of acute kidney disease before severe symptoms and complications develop.Conclusions. There is necessity to find early, easy and cheap markers of acute kidney injury which help decide if use renal replacement therapy. It increases the effectiveness of treatment and improves prognosis in this group of patients.